Correlation between momentum and ball speed in shooting movements of female futsal players - Agustiyanta; Satria Yudi Gontara; Rumi Iqbal Doewes; Ahmad Septiandika Adirahma (Universidad de Murcia, 2023)
Article accepted. The article will be published here soon. Pending final quality checks.